Hidden in plain sight: the (other) danger of COVID-19. Issue 4 (August 2021) - Pikkel, Yoav Yechezkel; Duek, Ori Samuel; Ben Naftali, Yeela; Link, Yuval; Khayr, Majd; Ullmann, Yehuda
Abstract : The Novel Coronavirus disease (COVID-19) first emerged in Wuhan province, China, in late November 2019 and changed public healthcare perception. It has caused a significant decline in attendance to outpatient clinics. However, other diseases have not stopped, including malignant melanoma. Survey of the number of visits to plastic surgery outpatient clinic during the first lockdown in Israel concerning malignant melanoma was compared to the same months in the previous years. We assessed the number of visits to the oncology department during 2020 compared to the number of visits and treatment protocols for malignant melanoma. During the first lockdown, the attendance at the plastic surgery outpatient clinic and ambulatory surgery decreased significantly ( P = 0.002), both in excisions of suspected malignant melanoma and malignant melanoma follow-ups ( P = 0.019 and P = 0.035, respectively). The last third of 2020 (from September to December) had shown a significant rise in new protocols commenced ( P < 0.001). This rise in the final third of the year was not noted in 2018 or 2019. These data clearly show the rise in advanced and metastatic malignant melanoma cases due to refraining from medical follow-ups and treatments during the COVID-19 pandemic. Diseases other than COVID-19 have not vanished, and continue to treat those diseases. Ignoring malignant melanoma treatment because of COVID-19 and vice-versa will not benefit our patients.